A NEW SPECIES OF RHINACANTHUS (ACANTHACEAE) FROM SRI LANKA - Amarasinghe, A. P. P. R.; Wijesundara, D. S. A. (Edinburgh Journal of Botany, 2011)
A new species, Rhinacanthus flavovirens Amarasinghe & Wijesundara (Acanthaceae), from Sri Lanka, is described and illustrated. It is compared with the closely allied Rhinacanthus nasutus and R. polonnaruwensis. A key to Rhinacanthus species in Sri Lanka is also presented.
Keywords: Acanthaceae; Rhinacanthus; Sri Lanka